Garlic Exosomes Promote Hair Growth Through the Wnt/?-catenin Pathway and Growth Factors - Yuksel, Esma Inan; Cicek, Demet; Demir, Betul; Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Yildirim, Merve (Springernature, 2023)
Background Exosomes are membrane-derived nanovesicles produced by cells and play an important role in intercellular communication. Objectives This study aimed to investigate the effects of garlic exosome (GE) on hair growth. Methods Forty-two Sprague-Dawley/Wistar albino rats were randomly divided into six groups: non-shaved control, shaved control, topical control, GE 2 mg, GE 4 mg, and topical GE. At the end of the experiment, the number of hair follicles, follicle diameter, and subcutaneous tissue thicknesses were measured histopathologically. The Wnt-1, beta-catenin, platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor-beta 1 (TGF-beta 1), and collagen I levels were measured by the Western Blot method. Results The anagen follicle counts of the GE 2 mg, 4 mg, and topical GE groups were 66.57 +/- 15.49, 105.71 +/- 25.06, and 55.29 +/- 6.72, and were significantly higher than the control groups (p<0.01, p<0.001 and p<0.05, respectively). The follicle diameter of the GE 4 mg group was higher than the others (p<0.05). The Wnt-1, PDGF, VEGF, TGF-beta 1, and collagen I levels of all GE groups, and the beta-catenin levels of the GE 4 mg and topical GE groups were significantly higher than the control groups (p<0.05). Conclusion GE induces hair growth in rats via the Wnt-1, beta-catenin, VEGF, PDGF, and TGF-beta 1 signaling pathways.
Keywords: wnt signaling pathway; vascular endothelial growth factor; transforming growth factor beta; hair follicle; garlic; exosome